DOES INTENTION TO LEAVE MODERATE THE DARK TRIAD PERSONALITY AND EMPLOYEE'S VOICE BEHAVIOR? - Permadi A.; Wibawa I M.A. (Russian Journal of Agricultural and Socio-Economic Sciences, 2023)
Employee’s voice behavior is influenced by individual personality and situational factors. Individual personality in this study involves the dark triad personality consisting of Machiavellianism, psychopathy, and narcissism, while situational factor in this study is the intention to leave. The research was conducted at PT Pegadaian Area Denpasar 1 involving 166 populations’ frontline employees. The research sample is 115 people. Data collection was carried out through observation, interviews, and questionnaires. This study was designed using a quantitative approach in which research data is expressed in the form of numbers. This research is an associative causality study to determine the relationship and cause and effect of dark triad personality with voice behavior moderated by intention to leave. Data analyzed by SEM (Structural Equation Modeling) with Partial Least approach Square (PLS). The results of the study show that machiavellianism and narcissism are positively related and significant to employee’s voice behavior, but psychopathy is negatively related and significant to employee’s voice behavior. Intention to leave as moderation has a significant influence on the relationship between psychopathy and voice behavior, while when interacting with machiavellianism and narcissism the intention to leave is not significantly affect the two relationships.